Financial and Economic Evaluation of Germinated Barley cultivation in South of Red Sea Governorate - Hany Elshatla; Mahaba ElSayed Ahmed Mahaba; Ahmed Abd elhamid (New Valley Journal of Agricultural Science, 2021)
The research aimed to study the financial evaluation of the cultivar barley units in the Shalateen area in the Red Sea Governorate, as one of the means used in providing green fodder for animal feeding, especially sheep, goats and camels. The research led to a set of results, including: (1) net present value when the discount rate is 9% about 2.445 million pounds, which indicates the feasibility of investment in this activity. (2) the internal rate of Return(IRR) was about 33.53%, which is more than the borrowing interest of the capital represented by the prevailing commercial interest rate, which confirms the feasibility of investing in the activity of cultivated barley. (3) the benifit cost ratio was estimated at 1.176 any larger than one, which indicates the feasibility of the investment. (4) the Pay-back Period (PBP) was estimated at 1.714 years, which indicates the possibility of recovering the invested capital within two years from the start of the project . (5) the return on investment rate was about 27.12 %.(6) sensitivity analysis of barley cultivation units has been carried out, however, the internal rate of Return is still greater than the opportunity cost of capital investment in the community and therefore it is recommended to make the decision to accept investment in barley cultivation units. Therefore, the research recommends the need for expansion in the cultivation of cultivar barley, especially in desert areas with low pastoral Plants.